Distal perforator based cross leg flaps for leg and foot defects - Bhattacharya V; Reddy Ganji (Indian Journal of Plastic Surgery)
The cross leg fasciocutaneous flaps are less frequently indicated for distal leg and foot defects due to the availability of other alternative options. However they still remain one of the more realistic options for the surgeon in situations like unsuccessful attempt of free flaps, non-availability of ipsilateral proximal calf tissue, damaged distal perforators following trauma, burns, radiation etc., and inadequate reach beyond mid sole. In the present article we share our experience emphasizing the significance and use, with redefined indications and surgical technique of cross leg retrograde fasciocutaneous flaps for various distal leg and foot defects. We are of the opinion that these flaps are still useful as they continue to prove to be the flap of choice in demanding situations.